Response of Growth Performance, Blood Biochemistry Indices, and Rumen Bacterial Diversity in Lambs to Diets Containing Supplemental Probiotics and Chinese Medicine Polysaccharides - Chen, Huan; Guo, Beibei; Yang, Mingrui; Luo, Junrong; Hu, Yiqing; Qu, Mingren; Song, Xiaozhen (Frontiers in Veterinary Science, 2021)
To investigate the effects of probiotics and Chinese medicine polysaccharides (CMP) on growth performance, blood indices, rumen fermentation, and bacteria composition in lambs. Forty female lambs were randomly divided into four groups as follows: control, probiotics, CMP, and compound (probiotics+CMP) groups. The results showed that probiotics treatment increased the concentrations of blood glucose (GLU) and immunoglobulin G (IgG), and enhanced rumen microbial protein contents, but declined the value of pH in rumen fluid compared with the control (P <0.05). Furthermore, supplemental with CMP enhanced the average daily gain (ADG) and the contents of IgA, IgG, and IgM in serum, but decreased the F:G ratio compared with control (P <0.05). Besides, both CMP and compound (probiotics+CMP) treatments decreased the ratio of acetic acid and propionic acid compared with the control (P <0.05). High-throughput sequencing data showed that at the genus level, the relative abundance of Veillonellaceae_UCG-001 in probiotics group was increased, the relative abundance of Succiniclasticum and norank_f__Muribaculaceae in CMP group were enhanced, and the relative abundance of Ruminococcaceae_UCG-002 in compound group was raised compared with the control (P <0.05). In summary, supplemental with probiotics can promote rumen protein fermentation but decrease the diversity of bacteria in rumen fluid, however, CMP treatment increased the relative abundance of Fibrobacteria, changed rumen microbial fermentation mode, increased the immune, and ultimately improved the growth performance.